Constraints in Marketing of Agroforestry Produce in India - Venkat Reddy, E. (Indian Forester, 2011)
Agro forestry in India is being promoted since last three decades. Traditional agro forestry systems are being practiced in many parts of India. Small scale farmers in villages are facing constraints due to inadequate knowledge of the market for sale of their products and lack appropriate technical know how for undertaking agro forestry profitably. Government and Non Governmental Orgauizations can playa crucial role in imparting training to farmers in cultivation and trade of agro forestry tree produce through their extension related activities. Development of rural enterprises by orgauizing the small farmers in to groups and societies will help them in procuring quality planting materials and for marketing of their produce. The Government has to develop the infrastructural facilities in villages for the promotion of agro forestry produce. The value addition of agro forestry produce will help the farmer to derive greater profits. The farmers must be h"ained through extension mechauisms in value addition methods.